Construction of the "Internet Plus" Community Smart Elderly Care Service Platform. (24th December 2021) - Wang, Biying; Xu, Liangpeng
Abstract : With the rapid development of China's market economy and the increasing trend of population aging, the traditional community elderly care service model has exposed more and more problems, such as the imbalance between supply and demand, single service, and lack of flexibility. In response to these issues, this research attempts to explore the possible paths and practical challenges of applying the Internet, Internet of Things, mobile networks, big data, and cloud computing to community elderly care services. This research believes that the construction of the "Internet Plus" community smart elderly care services platform is a general trend. Innovating the traditional community elderly care service model is conducive to fully integrating elderly care resources and improving the quality of elderly care services.